Origin of groundwater in the Ica aquifer-Peru, based on environmental isotopes - Robles Silvestre, Joselito Jersin (2022)
The Ica Valley, located in central and western Peru, is the main valley with agro-export potential due to its high rates of productivity and quality, while the aquifer from which water is extracted faces intensive groundwater extraction, leading to a considerable drop in piezometric levels due to overexploitation of the aquifer. We have proposed a conceptual model to establish the interconnection between the rainfall that occurs in the upper basin and the Ica aquifer, as well as the recharge mechanisms. Additionally, an isotopic and geochemical monitoring network has been established at strategic points from the lower, middle and upper basins, for the evaluation of groundwater, surface water and precipitation, this has allowed us to understand that the Ica Aquifer is recharged mainly by water from medium elevations. and upper reaches of the basin and it is at these points where artificial recharge must be carried out through infiltration, since there is a direct interconnection through geological faults between the water coming from high elevations and the aquifer itself.